Efeitos do ultra-som terapêutico sobre o crescimento longitudinal do fêmur e da tíbia em ratos - Barreto, Alfredo Alcantara [UNESP]; Barreto, Romi Kawasaki Alcantara; Pereira, Hamilton da Rosa [UNESP]; Hosnne, William Saad [UNESP] (FapUNIFESP (SciELO), 2011)
Objectives: To determine the effects of ultrasound therapy on the femur and tibia growth in young rats. Method: Four-week-old male Ratus Norvegicus totaling 115 animals, divided into four groups, were submitted to ultrasound therapy (0.8 MHz, fixed tube head, continuous pulse, for 10 minutes, once a day, ten times) on the medial face of the right knee, with powers of 0.0 W/cm2 (group G1), 0.5 W/cm2 (group G2), 1.0 W/cm2 (group G3), and 1.5 W/cm2 (group G4). Histological slides of the epiphysis, growth plate and metaphysis and the femoral and tibial length measurements were studied in the sixth, thirteenth and twenty-sixth weeks of life. The data were submitted to factorial analysis of variance according to a one-way layout. Results: No statistically significant bone growth alteration was established between any of the three treated groups and the control group. However, alterations in femoral and tibial growth suggesting a decrease in G4 in relation to G2 and G3 were noted. In G4, histopathological alterations, such as cellular necrosis and post-necrosis bone neoformation were found. Conclusion: According to this study, no statistical evidence of bone growth stimulus or inhibition resulting from the application of ultrasound therapy was found when comparing the treated groups with the control group. Histological alterations regarded as pathological were only observed in G4. Also, smaller significant bone growth was found in G4 compared to G2 and G3. Level of Evidence: Level II, cross-sectional study.
Effects of therapeutic ultrasound on longitudinal growth of the femur and tibia in rats
Keywords: Bone development; Epiphyses; Rats; Ultrasound therapy